Perceived associations between excessive sugar intake and health conditions - Prada, M. (2022)
Excessive sugar intake represents an increased risk of developing non-communicable diseases (e.g., obesity, cardiometabolic diseases, and dental diseases). Still, it is unclear whether people are aware of these adverse health outcomes. The current study systematically examined the extent to which people associate health conditions with excessive sugar intake. Participants (N = 1010 Portuguese volunteers) freely reported all health conditions they associated with excessive sugar consumption and rated the strength of these associations for eight specific health conditions. All participants reported health conditions associated with excessive sugar intake, with the most frequent being risk factors for cardiometabolic diseases (e.g., diabetes), cardiovascular diseases, oral problems, oncological and mental health conditions. Moreover, participants considered diabetes, overweight/obesity, and oral problems as being the conditions most related to excessive sugar intake. Women, participants with children in the household, and experts in health/nutrition rated excessive sugar intake as being more strongly linked to some of the health conditions. The identification of the health conditions that people associate with excessive sugar consumption may inform policymakers, educators, and health professionals and support interventions targeting the general public or specific groups (e.g., overweight people) in raising awareness of potential adverse health outcomes and, ultimately, contribute to reducing sugar intake.